Pemberdayaan Usaha Mikro Kecil Menengah (UMKM) Melalui Digital Marketing di Masa New Normal - Naila Fauza; Erningsih Erningsih; Melisa Carolina; Duta Wira Abhyasa Oeli; Elsa Martha Murni; Gratchia Saragih; Kevin Marcelino Harianja; Nadia Adam Sulistiowati; Silvia Widya Wati; Naufal Nata Prawira; Chiara Utami Sandra (Journal of Community Engagement Research for Sustainability, 2022)
The world is being hit by a covid-19 pandemic, including Indonesia. To break the chain of spreading of the virus, The government ask everypeople to stay at home. This situation has an impact on economic instability and affected to Micro, Small and Medium Enterprises (MSMEs). The purpose of this community service activity is to increase understanding, skills and added value in marketing products of Micro, Small and Medium Enterprises (MSMEs) affected by the Covid19. Community service activity is a qualitative approach. The method used is interviews and observations in the culinary business sector. The object of this research is MSMEs Dapur 12 Berseri, located in Sungai Pelunggut Village, Sagulung District, Batam City. The study describes some of the obstacles experienced by MSMEs Dapur 12 Berseri is the product marketing process. So, the empowerment most needed by MSMEs is the empowerment of online products marketing through the digital marketplace platform. The result of this community service activity is increase of understanding and the income earned by partners.